Comparison of Topical Application of TSG-6, Cyclosporine, and Prednisolone for Treating Dry Eye. Issue 4 (April 2016) - Kim, Yu Jeong; Ryu, Jin Suk; Park, Se Yeon; Lee, Hyun Ju; Ko, Jung Hwa; Kim, Mee Kum; Wee, Won Ryang; Oh, Joo Youn
Abstract : Purpose: To compare the therapeutic effects of topical tumor necrosis factor (TNF)-α–stimulated gene/protein-6 (TSG-6) with those of cyclosporine and prednisolone eye drops in NOD.B10.H2 b mice, a model for inflammation-mediated dry eye. Methods: The 12-week-old NOD.B10.H2 b mice were topically administered recombinant TSG-6 (0.1%) 4 times a day, 0.05% cyclosporine (Restasis) twice a day, or 1% prednisolone (Pred Forte) 4 times a day for 1 week. Aqueous tear production was measured by phenol red thread test, and corneal epithelial damage was observed with lissamine green and terminal deoxynucleotidyl transferase dUTP nick end labeling staining. Conjunctival goblet cell number was evaluated with periodic acid–Schiff staining. The levels of inflammatory cytokines were analyzed in the ocular surface (cornea and conjunctiva) and intraorbital gland. The dose-dependent effects of topical TSG-6 (0.001, 0.01, and 0.1%) were tested. Results: Tear production and goblet cell density were significantly increased in all groups receiving TSG-6, cyclosporine, and prednisolone. Corneal epithelial staining was markedly reduced by TSG-6 and cyclosporine but not by prednisolone. In prednisolone-treated eyes, corneal epithelial thickness was decreased, and apoptosis of corneal epithelial cells was increased. The levels of interferon gamma and TNF-α in the ocular surface and intraorbital gland were significantly repressed by TSG-6 and cyclosporine, and prednisolone treatment significantly reduced the level of interferon gamma. The effects of TSG-6 on the ocular surface and tear production were dose dependent. Conclusions: Topical TSG-6 was as effective in inflammation-mediated dry eye as cyclosporine eye drops. Topical prednisolone suppressed inflammation but induced apoptosis in the corneal epithelium.